The Position of Bills Of Lading in The Carriage of Goods at Sea - Andrew, Febren; Purwanto; Hediati, Febri Noor (Universitas Islam Lamongan, 2024)
ABSTRACT Legal rules for the transport of goods on an international scale are contained in three international conventions, namely The,Hague-Visby,Rules,1968, The Hamburg Rules 1978, and The,Rotterdam,Rules 2008. Meanwhile, on a national scale, they are regulated in the Criminal Code. In the activity of transporting documents used is a bill of lading or bill of lading. The bill of lading document used as the basis of this research is the bill of lading owned by PT. SPIL. The purpose of this study is of course to analyze documents for transporting goods such as bills of lading and explain the implications of issuing bills of lading belonging to PT. SPIL and the position of the bill of lading in agreements for the carriage of goods at sea in relation to the legal relations governing them. In addition to the location of the bill of lading which differs from each regulation, this also affects the legal consequences of issuing a bill of lading owned by PT. SPIL when viewed from legal regulations such as the Criminal Code, Criminal Code and the three international conventions and settlement of disputes that occur in the activity of transporting goods at sea. In carrying out the issuance of bills of lading, caution, accuracy and thoroughness are required. If you are not careful in issuing a bill of lading, it can lead to confusion.